ROLE OF LOCUS OF CONTROL AND UNDERSTANDING OF ACCOUNTANT ETHICS ON ACCOUNTANT ETHICAL BEHAVIOR - Kristianti, Ika Puspita; Kristiana, Deranika Ratna (Jurnal Reviu Akuntansi dan Keuangan)
The purpose of this study is to analyze the different level of moral reasoning ability in the accounting profession, measure individual ethical behavior using an experimental approach of hypothetical situations, and empirically test the influence of locus of control, individual demographical characteristics and the accountant’s understanding of the code of ethics into the accountant’s ethical behavior. This study use the basic theoretical framework of Kohlberg’s Moral Development Theory in explaining and predicting the relationship of individual ethical behavior with its demographic characteristics. This study also tries to modified study which analyze the relation of position level at work with individual ethical behavior, and added some variables: locus of control which referred to Rotter’s and the accountant’s understanding of the code of ethics. This study is a quantitative study using a survey method to find the effect of independent variables, partially and simultaneously to ethical behavior. We analyze sample responses of 96 respondents who works as an accountant in financial industries include banks and non-banks. The result shows that locus of control and the accountant’s understanding of the code of ethics relates positively and significantly to accountant’s ethical behavior, while demographic characteristics are not a predictor of ethical behavior among accountant profession